Evaluasi Kebijakan Analisis Jabatan di Komisi Pemilihan Umum Provinsi Jawa Timur - Ananda Citra Daymonna; Weni Rosdiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study evaluates the implementation of the Job Analysis (Anjab) policy at the Provincial General Elections Commission (KPU) of East Java using William N. Dunn’s policy evaluation model. The purpose of this research is to assess the extent to which the Anjab policy has been effective, efficient, adequate, equitable, responsive, and appropriate in supporting human resource management within the Provincial KPU. This study employs a descriptive qualitative approach, with data collected through interviews with personnel in the Subdivision of Personnel, observations, and document analysis of relevant regulations and internal documents. The evaluation shows that the implementation of Anjab within the KPU has not been optimal, as the Anjab documents have not been updated regularly, the job map remains generic and nationally standardized, there is no dedicated team responsible for Anjab management, and personnel’s understanding of Anjab remains limited. These conditions result in discrepancies between job descriptions and actual tasks performed, disproportionate task distribution, and low utilization of Anjab in human resource structuring. Consequently, the policy has not been fully effective, efficient, responsive, or well-targeted. Key recommendations include establishing an Anjab implementation team, providing technical training, developing an institution-specific job map, and conducting regular document updates